The Role of Mathematics Teachers in Providing Students with Mental Arithmetic Skills from The Teachers’ Point of View in Public Schools in Ajloun Governorate - Al-Momani, Abdelhamed Mohamed Abdelhamed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the role of mathematics teachers in providing students with mental arithmetic skills from the teachers’ point of view in public schools in Ajloun Governorate, and to identify the degree to which mathematics teachers practice the strategies of teaching mental arithmetic skill. The researcher used the descriptive approaches, study Sample consisted from (120) Female and male mathematics teacher, chosen randomly, to collect data Questioner used. The result of SPSS analysis shown that the role of mathematics teachers in providing students with mental arithmetic skills from their perspective was moderated with average (2.96 out of 5), and the degree to which mathematics teachers practice the strategies of teaching mental arithmetic skill was moderated with average (3.62 out of 5), The finding also showed there wasn’t any statistically significant differences at (α≤0.05) refers to school teacher sex (male and female). In addition, there were statistically significant differences refers to teacher years of experience and in favor of 10 years and less.